2016
DOI: 10.1080/14616734.2016.1261915
|View full text |Cite
|
Sign up to set email alerts
|

Categorical and dimensional approaches in the evaluation of the relationship between attachment and personality disorders: an empirical study

Abstract: Although several studies have highlighted the relationship between attachment states of mind and personality disorders, their findings have not been consistent, possibly due to the application of the traditional taxonomic classification model of attachment. A more recently developed dimensional classification of attachment representations, including more specific aspects of trauma-related representations, may have advantages. In this study, we compare specific associations and predictive power of the categoric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
3
12
0
2
Order By: Relevance
“…Moreover this is coherent with the idea that interpersonal disturbances are central in BPD (e.g. [ 49 ]) and with attachment [ 45 , 50 ] and mentalization research [ 46 ].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover this is coherent with the idea that interpersonal disturbances are central in BPD (e.g. [ 49 ]) and with attachment [ 45 , 50 ] and mentalization research [ 46 ].…”
Section: Discussionsupporting
confidence: 83%
“…Although most studies have reported on the AAI unresolved state of mind as a categorical variable, in recent years, it has been increasingly used as on a continuous scale of severity, as it increases statistical power (Hesse, ; Hughes et al, ; Thomson & Jaque, ). This is in line with more recent research, which has investigated the usefulness of scoring the AAI on continuous scales to arrive at a dimensional understanding of attachment representations (Chiesa, Cirasola, Williams, Nassisi, & Fonagy, ; Roisman, Fraley, & Belsky, ).…”
Section: Discussionsupporting
confidence: 86%
“…In order to maintain at least a form of positive relatedness with the meaningful others and a sense of personal worthiness and autonomy, the BPD patients are supposed to split the angry and raging aspects of their personality from their self-representation and from the experience of their relationship with outer world ( Kernberg, 1975 ). BPD patients are reported to experience such an unbearable amount of anger given their proneness to perceive personal threats in the outside world, mainly in close relationships, owing to both temperamental factors ( New et al, 2008 ; Gunderson, 2010 ) and early traumatic experience in the attachment matrix ( Chiesa et al, 2016 ). As a result, anger reactions are easily elicited as a basic defensive (flight-fight) response to the feeling of being attacked.…”
Section: Personality Building and The Metabolism Of Anger/ragementioning
confidence: 99%